Adventure Tourism: The new frontier: A Critical Review - Bajracharya, Ramesh Kumar (Journal of Tourism and Himalayan Adventures, 2021)
Writers: John Swarbrooke, Colin Beard, Suzanne Leckie & Gill Pomfret Publisher: Butterworth-Heinemann An imprint of Elsevier Science Linacre House, Jordan Hill, Oxford OX2 8DP 200 Wheeler Road, Burlington MA 01803 First published 2003, Copyright © 2003, Elsevier Science Ltd. All rights reserved